Assembly of vesicular stomatitis virus nucleocapsids in vivo: a kinetic analysis. - Hsu, C H (1979)
Pulse-chase labeling and cell fractionation were used to examine the pathways taken by the three nucleocapsid polypeptide species of vesicular stomatitis virus into nucleocapsids and then into virions. An improved method of polyacrylamide gel electrophoresis resolved nucleocapsid polypeptides N and NS from cellular actin, facilitating accurate quantitation of the viral polypeptides. Contrary to previous belief, the rate of NS synthesis was found to be a constant fraction of total virus protein synthesis throughout infection, indicating a consistent mechanism of virus protein synthesis regulation. In the kinetic studies, each polypeptide species displayed the following characteristic behavior. (i) Structural polypeptide N was the only species that entered a metabolically active soluble pool before assembly into nucleocapsids. The size of this pool increased with time after infection, causing an increasing delay in the appearance of pulse-labeled N molecules in nucleocapsids. (ii) Throughout infection, the entire complement of L molecules entered nucleocapsids immediately after their synthesis, without diversion through a soluble pool. (iii) Although 75% of newly synthesized molecules of the transcriptase-associated protein NS entered a soluble pool, they never emerged from the compartment. At all times after infection, about 25% of the NS molecules bypassed the soluble pool and entered nucleocapsids directly after their synthesis, as if in concert with L. These results indicate that VSV nucleocapsid assembly in vivo is a stepwise process, comprising an initial condensation of N with the viral RNA, followed by attachment of L and NS, analogous to the stepwise assembly of Sendai virus nucleocapsids. (D. W. Kingsbury, C.-H. Hsu, and K. G. Murti. Virology 91:86-94, 1978). About half of the intracellular nucleocapsids were recovered in a form that sedimented at anomalously low centrifugal forces, reflecting an association with large cellular organelles. This attachment was mediated mainly by electrostatic forces, since these "bound" nucleocapsids were released by elevated salt concentrations. The kinetic behavior of nucleocapsid polypeptides was the same in both fractions, providing no evidence for a division of nucleocapsid functions between cellular compartments.